Metformin therapy and risk of cancer in patients after heart transplantation - Bedáňová, Helena; Horváth, Vladimír; Ondrášek, Jiří; Krejčí, Jan; Dobšák, Petr; Němec, Petr (Bratislavské lekárske listy, 2021)
BACKGROUND: Diabetes mellitus (DM) and malignancy are recognized among the most common complications increasing mortality in patients after heart transplantation (HTx). Clinical trials have shown a higher risk for different types of tumours in diabetic patients. This risk is potentiated by immunosuppressive therapy in transplant patients. Biguanide metformin has been shown to exhibit anti-tumour activity and we tried to fi nd out whether this effect is valid for heart transplant patients. METHODS: We retrospectively analysed a group of 497 patients, who undergone HTx in our centre between 1998 and 2019. The primary outcome was any malignancy during the 15-year follow-up period and patient’s survival. RESULTS: Out of the 497 patients enrolled in the study, 279 (56 %) had diabetes and 52 (19 %) were treated with metformin. Fifteen-year survival in treated patients without malignancy was 93 %, the remainder for the DM patients was 56 %, with survival in non-DM patients being 74 %. Untreated diabetic patients had 4.7 times higher chance of malignancy than those on metformin (p = 0.01). Fifteen-year survival in metformin treated patients was 53 %, in other DM patients 44 %, and in non-DM patients 51 %. CONCLUSION: Our study showed a signifi cantly lower incidence of malignancies in metformin-treated patients and slightly better overall survival (Tab. 2, Fig. 3, Ref. 19).
Keywords: Heart Transplantation; dospělí; Kaplan-Meier Estimate; Female; metformin; Adult; ženské pohlaví; Kaplanův-Meierův odhad; Neoplasms; nádory; diabetes mellitus; lidé; Survival Analysis; Metformin; Male; riziko; Diabetes Complications; transplantace srdce; analýza přežití; Diabetes Mellitus; lidé středního věku; mužské pohlaví; Risk; komplikace diabetu; Middle Aged; Humans